2011
DOI: 10.1097/nmc.0b013e31821826e7
|View full text |Cite
|
Sign up to set email alerts
|

The Process of "Persevering Toward Normalcy" After Childbirth

Abstract: In the early weeks postpartum, women can be taught how and when to access social support to promote sleep and prevent severe fatigue. Instruction on sleep hygiene and infant day/night entrainment may help women maximize sleep opportunities and infants establish a routine. To provide effective assistance, it is also necessary to understand the woman's individual sleep environment, as well as her socioeconomic and cultural contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…As in other research, breastfeeding participants reported that flexible practices of infant care enabled them to get more sleep (Doering & Durfor, 2011). We found among the formula-feeding participants that personal behavioural choices were guided by authoritative cultural norms (Chianese, Ploof, Trovato, & Chang, 2009).…”
mentioning
confidence: 58%
“…As in other research, breastfeeding participants reported that flexible practices of infant care enabled them to get more sleep (Doering & Durfor, 2011). We found among the formula-feeding participants that personal behavioural choices were guided by authoritative cultural norms (Chianese, Ploof, Trovato, & Chang, 2009).…”
mentioning
confidence: 58%
“…Despite recognition of the potential dangers resulting from sleepy employees [29] there has been little attempt to understand sleepiness in new parents returning to work. This oversight within the literature has further consequences when considered that despite high levels of sleepiness, new mothers “persevere” to meet their essential work and economical demands [30]. Future research should consider practical implications for high risk activities, such as driving, and the potential impact of self-limiting risk exposure behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Postpartum mothers describe the necessity to persevere through their sleep disturbance in order to work and meet essential economical demands (Doering & Dufor, 2011). Similarly, new fathers have been shown to return to work despite their high level of fatigue, which is consequently inversely associated with work safety behaviors (Mellor & St John, 2012).…”
Section: Discussionmentioning
confidence: 99%